Characterization of the Hydrogen Migration in a VT1-0 Titanium Alloy by Thermo-EMF and Eddy Current Nondestructive Control Methods; Russian Metallurgy (Metally); Vol. 2020, iss. 11 - Xu Shupeng; Larionov V. V. Vitaliy Vasilyevich; Kudiyarov V. N. Victor Nikolaevich; Elman R. R. Roman Romanovich; Lider A. M. Andrey Markovich (2020, 2020)
Title screen